Sensor fusion: let's enhance the performance of performance enhancement - Lee, J. B.; Ohgi, Y.; James, D. A. (Procedia Engineering, 2012)
Typical in-filed technology used for human movement assessment is a single tool such as a video camera. However, there are drawbacks with this system. Understanding various human actions e.g. swimming kinematics, or the legality of a bowling action in cricket, is important for performance analysis. Inertial sensors can biomechanically capture temporal kinematics. Measuring the kinematics of human movement, allows performance analysers to monitor progression of an athlete's development. Fusing video and inertial sensor technology supplies visual feedback in conjunction with technical information. The video-sensor fusion presented here provides assessment for athletes where gross visual measures combined with fine movement monitoring possible. Therefore, a novel system can be offered which can assist athlete performance development.